2019
DOI: 10.1101/605204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining composition and function of the rhizosphere microbiota of barley genotypes exposed to growth-limiting nitrogen supplies

Abstract: BackgroundSince the dawn of agriculture, human selection on plants has progressively differentiated input-demanding productive crops from their wild progenitors thriving in marginal areas. Barley (Hordeum vulgare), the fourth most cultivated cereal globally, is a prime example of this process. We previously demonstrated that wild and domesticated barley genotypes host distinct microbial communities in their rhizosphere. Here we tested the hypothesis that microbiota diversification is modulated by, and in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 185 publications
(277 reference statements)
0
14
0
Order By: Relevance
“…Yet, a recent study conducted on maize demonstrated that Proteobacteria, specifically members of the family Oxalobacteraceae, promote lateral root density and shoot dry weight (proxies for plant growth) under nitrogen limiting conditions ( Yu et al, 2021 ). As the soil tested in our experiments is limited in the availability of nitrogen for barley growth ( Terrazas et al, 2019 ) and considering the enrichment of putative ammonia oxidizers archaea in the rhizosphere of treated plants (see above), it can be speculated that the differential Proteobacterial enrichment triggered by gramine application may be linked to nitrogen turnover in the rhizosphere. An additional observation derived from these experiments is that gramine application triggers a differential microbial recruitment in the two tested genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a recent study conducted on maize demonstrated that Proteobacteria, specifically members of the family Oxalobacteraceae, promote lateral root density and shoot dry weight (proxies for plant growth) under nitrogen limiting conditions ( Yu et al, 2021 ). As the soil tested in our experiments is limited in the availability of nitrogen for barley growth ( Terrazas et al, 2019 ) and considering the enrichment of putative ammonia oxidizers archaea in the rhizosphere of treated plants (see above), it can be speculated that the differential Proteobacterial enrichment triggered by gramine application may be linked to nitrogen turnover in the rhizosphere. An additional observation derived from these experiments is that gramine application triggers a differential microbial recruitment in the two tested genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing reads were processed using a customized bioinformatics pipeline as described before ( Terrazas et al, 2019 ). Briefly, sequencing reads were subjected to quality assessment using FastQC ( Andrews, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…An alternative, not mutually exclusive scenario, is a differential rate of gramine degradation in the rhizosphere (Ghini, Burton & Gros, 1991) of the two genotypes as this would alter the bioavailability of this compound to the resident members of the microbiota. Regardless of the scenario, it is interesting to note that gramine applications failed to trigger a sustained enrichment of members of the Actinobacteria, which can be considered as a hallmark of elite, gramine-free, barley genotypes grown in the same soil type (Alegria Terrazas et al, 2020) and in other modern/ancestral plant pairs (Pérez-Jaramillo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing reads were processed using a customized bioinformatics pipeline as described before (Terrazas et al, 2019). Briefly, sequencing reads were subjected to quality assessment using FastQC (Andrews et al, 2015).…”
Section: Amplicon Sequencing Reads Processingmentioning
confidence: 99%
“…For instance, experimental data indicate that abundance of phytoavailable nitrogen, i.e., the scenario of mineral fertiliser treatments, tend to repress the proliferation and activity of members of the microbiota (Ramirez et al, 2012; Terrazas et al, 2019), and this in turn may be reflected in the metabolism of secondary compounds (terpenoid and polyketide metabolism) and membrane transport (ABC transporters).…”
Section: Discussionmentioning
confidence: 99%